The story of architecture of the 20th century - Tietz, Jürgen, 1964- (Konemann, 1999)
"Our everyday life is conditioned to a significant degree by the 20th century architecture that surrounds us each day - at home, in the workplace, out shopping. Even during our leisure time, at the pool or in the football stadium, or at the museum, architecture creates the necessary architectural environment for our activity. Without architecture, human society would be impossible." This book looks at the architecture that surrounds us in our lives.--p. 6.